Efficiency and profitability of pearl millet production in the North-West region of Nigeria - Mukhtar, Umar (2018)
This study was conducted to investigate the efficiency and profitability of pearl millet production in northwest region of Nigeria. Primary data were collected from 430 pearl millet farmers through the use of structured questionnaires. Systematic random sampling technique was used for this study. Analytical techniques used for analysis were descriptive statistics, net farm income, OLS and stochastic frontier production model. The descriptive statistics results shows that the respondents had mean age of 39 years with 10.7 years of pearl millet production experience. Greater portion of the respondents (92.60 percent) were males and most of them (67.00 percent) were married. Majority (28.8 percent) of the farmers cultivated between 1.5 to 2.4 hectares of land during 2013/2014 seasons, and about (50 percent) of them acquired their farmland through inheritance. The average household size was 7 persons, while about (43.72 percent) of the farmers had no extension contact during the 2013/2014 cropping season. Although, majority of the farmers (79.30 percent) had formal education, but about (53 percent) of them did not belong to any farmers’ cooperative societies. Majority of the farmers (68.8 percent) had no access to credit facilities and higher proportion of them (44.78 percent) sourced their finance through internal financing. Most of the farmers (35 percent) earned between $159 and $945 annually as income from pearl millet farming. The results from farm budgeting techniques show that seasonal profitability analysis on per hectare basis with regard to pearl millet production in the study area revealed that a total revenue of $463.24; total cost of production of $262.35; gross margin and net farm income of $233.89 and $200.89 respectively were realized. Also, PI, RRI and CTO of 0.43, 0.77 and 1.77 respectively were generated. The farm inputs costs that affect profitability of pearl millet production were found to include cost of renting land, cost of fertilizer, cost of labour, cost of seed, cost agrochemicals and output price were the farm inputs costs found to be associated with profitability. The results obtained from the stochastic frontier analysis shows substantial technical, allocative and economic inefficiencies among smallholder pearl millet farmers. The results reveals that all the six production variables used in the model; farm size, fertilizer, manure, labour, seed, and agrochemical had a positive technical relationship with pearl millet output and were statistically significant. The elasticity of production with value of 1.83 showed that the pearl millet farmers were operating at an increasing return to scale. The result also reveals an average TE of 82 percent. The best practicing and the least technically efficient pearl millet farmers had technical efficiencies of 96 and 64 percent, respectively, while AE estimates ranges from 30 to 91 percent with a mean of 68 percent. The mean EE is 59 percent, with a minimum being 16 percent and a maximum of 90 percent. The results therefore indicate that inefficiency in pearl millet production in north-western Nigeria is dominated by allocative and economic inefficiency. In addition, in the OLS models, farmers’ socio-economic factors such as farm size of farmers, type of seed, household size, education, access to credit and extension contact were found to determine technical efficiency. On the other hand, age of farmer, farm size, farming experience; cooperative membership, extension contact and distance to market have positive effects on allocative efficiency of pearl millet farmers. In a similar case, farm size, education, experience, type of seed, cooperative membership, credit and extension contact are the major determinants of economic efficiency. Results of the study revealed a need for strong policies towards ensuring an efficient means of accessing farmland, fertilizer, labour and improved pearl millet varieties accesses. Also, the creation of co-operative societies or joining existing ones should be encouraged. Policies should also be formed to ensure easy and timely access to credit to pearl millet farmers as well as strengthen the extension programs for effective extension services delivery in the study area.